Association of Hemodynamic Behavior in the Thoracic Aortic Aneurysm to the Intraluminal Thrombus Prediction: A Two-Way Fluid Structure Coupling Investigation - Ong, Chi Wei (IMPERIAL COLLEGE PRESS, 2021)
10.1142/S1758825118500357